DINASTI POLITIK DALAM PEMERINTAHAN LOKAL STUDI KASUS DINASTI KOTA BANTEN - Winda Roselina Effendi (JURNAL TRIAS POLITIKA, 2018)
Abstract Political dynasties can be understood as a political strategy to maintain power by passing down the power that has been held by others who are still among relatives. First, the stagnation of the cadre of political parties in capturing qualified regional head candidates, thus creating political pragmatism by encouraging relatives the regional head's family to become a public official. Second, the context of the community that maintains the status quo conditions in the region that want the regional head to rule by encouraging the family or people close to the regional head to replace detention. Political dynasty is a negative excess of regional autonomy that makes hijacked democracy by the circulation of genealogical core relations, based on kinship relations and outside of genealogical lines that have an interest in perpetuating family power. In practice, the actualization of political dynasties is carried out with several perspectives, namely neopatrimonialism, political clan, and political predators.  The development of political dynasty at the local level can also be interpreted as a form of local 'Cendanaisasi'. The term cendanaisasi refers to the Cendana Family during the 32 years of President Soeharto's leadership which was very powerful in Indonesia's political economy. All key government posts are controlled by children, sons-in-law, nephews, and other relatives, so that this power becomes lasting for three decades of government. This pattern is actually being developed and exemplified by local elite families that the local democratic process can be traced by placing relatives in regional strategic positions. Keywords: Local Politics, Dynasty, Regional Government  Abstrak Dinasti politik dapat dipahami sebagai strategi politik untuk tetap menjaga kekuasaan dengan cara mewariskan kekuasaan yang telah digenggam kepada orang lain yang masih merupakan kalangan sanak keluarga, Pertama, macetnya kaderisasi partai politik dalam menjaring calon kepala daerah yang berkualitas, sehingga menciptakan pragmatisme politik dengan mendorong kalangan sanak keluarga kepala daerah untuk menjadi pejabat publik. Kedua, konteks masyarakat yang menjaga adanya kondisi status quo di daerahnya yang menginginkan kepala daerah untuk berkuasa dengan cara mendorong kalangan keluarga atau orang dekat kepala daerah menggantikan petahanan. Dinasti Politik merupakan ekses negatif dari otonomi daerah yang menjadikan demokrasi terbajak (hijacked democracy) oleh sirkulasi hubungan inti genealogis, berdasarkan relasi kekeluargaan maupun di luar garis genealogis yang memiliki kepentingan terhadap pelanggengan kekuasaan family. Dalam prakteknya sendiri aktualisasi dinasti politik dilakukan dengan beberapa sudut pandang yaitu neopatrimonialisme, klan politik, dan predator politik. Berkembangnya dinasti politik di tingkat lokal juga bisa ditafsirkan sebagai bentuk ‘Cendanaisasi’ lokal. Istilah cendanaisasi merujuk pada Keluarga Cendana semasa 32 tahun kepemimpinan Presiden Soeharto yang sangat berkuasa dalam ekonomi-politik Indonesia. Semua pos-pos kunci pemerintahan dikuasai anak, menantu, kemenakan, maupun kerabat lainnya, sehingga kekuasaan tersebut menjadi langgeng selama tiga dekade pemerintahan. Pola itulah yang sebenarnya sedang berkembang dan dicontoh oleh para keluarga elit lokal bahwa proses demokrasi lokal bisa ditelikung dengan menempatkan kerabat dalam posisi strategis daerah. Kata Kunci: Politik local, Dinasti, Pemerintahan daerah